JUSTICE AND EQUITY - Elena ANGHEL (Challenges of the Knowledge Society, 2017)
Juridical principles have a privileged place within the positive juridical order, representing foundation of the legal edifice: they prove the continuity of law during the centuries and that is why here we have to dig in order to find out the foundation of law, its permanent nature, its substance; they precede and give birth to positive law, which lies upstream of legal rules; principles build and direct the entire system of law, conferring to the legal order its necessary stability; being the underlayer of positive law, the principles of law represent a stability factor and, also, a source of unity, coherence, consistency and efficiency for that legal system1. The entire law science consists in reality of “generating from the multiplicity of law dispositions their essential, namely these exact last justice principles, from which all the other dispositions derive. Hereby, the entire legislation becomes of a great clarity and is caught in the so-called legal spirit”2.